Acetic acid and sodium chloride as mordants to Talahib grass (Saccharum, Spontancum, Linn.) dye - Bugayong, Kristin Salud Dela Cruz
This is an experimental study on the effectiveness of acetic acid and sodium chloride as the mordants to the dye from the talahib grass. The three sample fabirics used in the experiment were polyester-cotto (81%, 19% respectively), silk (100%) and pina-silk (56.6%, 43.4% respectively). A liquor ration 1:30 was used on the mordanting and dyeing processes where 1 g of fabric was used for every 30 ml of mordant solution and dye liquor. On the other hand, a liquor ratio of 5:30 was used in the color extraction, meaning 5 g of talahib grass was used for every 30 ml of water. Iodized sodium chloride was used in concentrations of 5%, 3%, and 1% while acetic acid was used in concentrations of 10%, 7% and 4%. Using acetic acid and sodium chloride as mordants produced a light brown color on the silk and pina-silk fabrics. However, there was very little color imparted on he polyester-cotton fabrics. The mordant concentration affected the brightness of the color of the dyed silk and pina-silk fabrics. But, as the concentration of sodium chloride increased, a darker color was obtained for both the fabrics. Because only silk and pina-silk fabrics exhibited color, these were only fabrics subjected to the colorfastness test to accelerated washing. Each fabric tested received a rating of 4.5 on color staining and 1.0 to 1.5 on color change. Although the fabric passed the test for color staining, they failed the test for color change. The overall result is that the dyed fabrics are not colorfast.